Perancangan dan Implementasi Algoritma Enkripsi Idea pada Perangkat Kriptografi Berbasis FPGA - Muhammad Adi Wijaya; Wijaya Kurniawan; Ari Kusyanti (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The use of text data applications is currently growing rapidly, even now many applications are switching to embedded systems. Many users choose to switch to embedded systems because they are more efficient, cheap, and have a fast response so it does not endanger the quality of the submitted text data. One of the embedded systems used today is the use of personal digital assistants or PDAs. The need for a PDA as a wireless communication tool is very important to be noticed, because the data sent through the communication may be company data that cannot be known by anyone. Tapping cellphones / PDAs on wireless communication often occurs. To solve the problem, information security is needed to complete the needs of the data security on PDAs / cellphones. Information security used to resolve these problems is using the IDEA algorithm. The IDEA algorithm is used because it provides high level security based on complex secret keys. The step taken to implement this algorithm is a system needs analysis to find out all the needs needed by the system to be built and tested, after that the system design is done using the Xilinx Spartan FPGA 3-e as a simulator before it can be designed directly on cryptoprocess integrated circuit, then the system design results will be implemented on the FPGA and will be displayed on the PC. After the system is implemented it will be tested and analyzed using functional testing, validity, and execution time. Based on the results obtained the text data encryption implementation with IDEA method can be implemented on FPGA Xilinx Spartan 3-e and generate ciphertext to encrypt existing data and test results using functional testing and validity give 100% correct system results and generate a text data encryption with text data encryption time of 7.788ns.